IMPLEMENTASI STRATEGI PEMBELAJARAN MENYIMAK MODEL DICTOGLOSS PADA GURU PESERTA PENDIDIKAN PROFESI GURU (PPG) PRA-JABATAN FKIP UNIVERSITAS SYIAH KUALA - Teuku Alamsyah; Ramli Ramli; Maya Safhida (Jurnal Dedikasi Pendidikan, 2023)
This study aims to (1) implement the dictogloss listening learning strategy and (2) record the advantages and disadvantages of the strategy based on the implementation results, and (3) produce recommendations for the feasibility of using this strategy to improve listening skills in learning Indonesian and English at the school level. medium. The sources of study data are Indonesian language subject teachers and English subject teachers who are members of the Pre-Occupational Teacher Professional Education (PPG) Batch I of 2022, FKIP Universitas Syiah Kuala. Research uses qualitative principles. Data was collected using documentation, observation, and interview techniques. Data analysis of the results of the study was carried out using the principles of qualitative data analysis. The results of the study show that the learning strategy for listening to the dictogloss model: (1) is in accordance with the demands of creative, innovative, and collaborative Indonesian and English learning as expected in the 2013 Curriculum, (2) is effective and efficient in its implementation, (3) can involve all students at the same time to be active in learning, (4) facilitate individual learning and group work, (5) activate schemata and cognitive aspects of students when reconstructing texts, (6) easy to design and implement by teachers, (7) precise and effective for a tool to measure students' listening skills, and (8) teachers can apply this dictogloss model listening learning strategy at all grade levels by making adjustments to reading texts based on Basic Competency demands